Morphological Proof of nerve regeneration after long-term defects of rat sciatic nerves. (2nd November 2015) - Jiao, Haishan; Yao, Jian; Song, Yuening; Chen, Ying; Li, Dongyin; Liu, Xiaomei; Chen, Xue; Lin, Weiwei; Li, Yi; Wang, Xiaodong
Abstract : Unsatisfactory efficacy of clinical cure for long-term delayed injuries and other disadvantages such as the low regeneration rate and speed of axotomized neurons and the questionable reinnervation ability of atrophic target organ lead to inaction to the long-term delayed injuries. Here we attempted to use autologous nerve to bridge a long-term delayed 10-mm defect in SD rats based on some previous positive messages of basic and clinical research. In this study, for experimental groups, the rat sciatic nerve had been transected leaving a 10-mm defect, which was maintained for 3 or 6 months before implantation with the autologous graft. The non-grafted animals served as negative control. Measuring with electrophysiological and histological techniques, we find: (1) A number of long-term axotomized neurons survived and sustained certain degree of axonal regenerative capacity; (2) A few denervated Schwann cells survived and retained their ability to provide trophic support and myelinate axons in at least 6 months; (3) the chronically denervated muscle can partially be reinnervated by regenerated axons. But the quantity and the quality of the regenerated nerve fibers and the reinnervated muscle fibers were all poor. Thus these observations provide new positive morphological proof of nerve regeneration after long-term defects and further studies will be needed to increase the survival rate and the regenerative speed of long-term chronic axotomized neurons, enhance the support provided by denervated distal stumps and protect the target muscle.